Penanaman Khauf dan Raja’ Dalam Pendidikan Karakter Remaja - Casmini Casmini; Taufik Nurfadhi; Putri Kusumaningrum (Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2021)
Planting khauf and raja' is urgent enough to be the foundation of youth's personality and character. This paper aims to describe the process of internalization of khauf and the king 'carried out by parents in its implementation to strengthen the character of adolescents. Research data was extracted through library research obtained from primary sources in the form of articles and corroborated with character education books. Secondary sources are articles in journals that implement Sufism in both Sufi life and the praxis of implementing Sufistic therapy. The results of the study describe that the planting of khauf and raja' is carried out continuously, through a process of internalizing the stages of forming habits, understanding, and producing spirituality. The character of honest, sincere, responsible, optimistic by releasing pride, and awareness that Allah Swt. the determinant of what is sought, then parents internalize the character of adolescents to wish only to God so that controlled and controlled behavior of adolescent life.